Computer Assisted Medicolegal Death Investigation in Pregraduate Medical Education a Model Study - Özdemir, Mehmet Hakan; Demiroğlu, Zehra; Ergönen, Akça Toprak; Salaçin, Serpil (The Bulletin of Legal Medicine, 2008)
Basic knowledge for forensic dead body examination is given at an awareness level to first year students of our medical faculty where a PBL programme is implemented. Postmortem changes, postmortem examination methods in forensic cases are given as comprehensive knowledge tools and skills training to the third year students in a specific module. In this one-week long module, computer and mannequin/model assisted practice are used for the forensic dead body examination skills training. At the beginning of this practice, a mini scenario is used to reach the learning objectives. The importance of the forensic inquiry, examination of the clothing and the body, determining the postmortem changes and the wounds are the learning objectives. The students are studying in small groups which are assisted by an educator. Students’ skill acquisitions are evaluated at the end of the block at a station similar to the practice. The aim of this paper is to introduce a computer and mannequin assisted forensic dead body examination practice in pregraduate education and to share our experiences about the process of the practice. Key words: Forensic medical education, forensic dead body examination, computer assisted education